Managing codified content for reuse in knowledge work. (22nd March 2021) - Bosua, Rachelle; Venkitachalam, Krishna
Abstract : Firm‐wide integrated organisational applications such as intranets, enterprise portals, content repositories, and wikis are often instrumental in supporting knowledge work. Serving as centralised "containers" of codified content that facilitate knowledge work, one essential requirement is continuous reuse and management of codified content. In this paper, our investigation aims to determine suitable perspectives to manage codified content, by focusing on one specific integrated organisational infrastructure application, namely intranets. Findings from three case studies identified three modes to manage codified content for knowledge work for enterprise content systems and are: (a) shared, (b) controlled, and (c) informal. In addition, based on the three modes (or ways), findings also highlight four elements that impact the management of codified content for knowledge work, that is, (a) content contributions, (b) content sharing, (c) access to expertise, and (d) control of codified content.